In vitro Prebiotic Properties of Garlic Polysaccharides and Its Oligosaccharide Mixtures Obtained by Acid Hydrolysis - Lu, Xiaoming; Li, Ningyang; Zhao, Renjie; Zhao, Meng; Cui, Xuanxuan; Xu, Yukun; Qiao, Xuguang (Frontiers in Nutrition, 2021)
Fructans and oligofructose are usually used as prebiotics without any limitation in functional food or food ingredients. Degree of polymerization of polysaccharides affects the utilization by probiotics. Garlic is rich of fructans. The objective of this work was to extract and purify polysaccharides from garlic, analyze its composition, hydrolyze them using HCl and then evaluate the prebiotic potential of the garlic neutral polysaccharides (GPs) before and after hydrolysis. GPs was 6.57×103 Da with a composition of fructose and glucose at a ratio of 4:1. After acid hydrolysis, low molecular weight fraction in garlic oligofructose (GOs)may be eliminated through ultrafiltration. The content of oligosaccharides with average degree of polymerization (DP) <10 increased from 15% to 75%. GPs and GOS had a stronger resistance to acid conditions in human stomach than FOS, and GOs showed better prebiotic properties on the growth of lactobacilli than GPs. This study evaluates the prebiotic potential of the garlic frutctans and oligosaccharides mixtures obtained by acid hydrolysis, which may be used as an ingredient in functional food and nutraceutical products.